2016
DOI: 10.1186/s12348-016-0087-y
|View full text |Cite|
|
Sign up to set email alerts
|

The role of oral co-trimoxazole in treating Nocardia farcinica keratitis: a case report

Abstract: Nocardia farcinica is one of the more recently identified species of the Nocardia genus. Nocardia farcinica keratitis is a rare occurrence, with only eight previously reported cases. Semi-permeable rigid contact lens use was associated with one of these reported cases. We report the first case of an extended wear soft contact lens-related Nocardia farcinica keratitis and recommend a new treatment regime. A 47-year-old lady presented with a right eye keratitis after wearing her extended wear soft contact lenses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…According to previous studies and drug susceptibility results, N. farcinica is sensitive to compound sulfamethoxazole and amikacin, and resistant to cephalosporins, tobramycin and ciprofloxacin. [5,18,19] It has been reported that vitreous body injection of amikacin may lead to macular necrosis. [20,21] However, there are no effective antibiotics that can control infection through anterior chamber injection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies and drug susceptibility results, N. farcinica is sensitive to compound sulfamethoxazole and amikacin, and resistant to cephalosporins, tobramycin and ciprofloxacin. [5,18,19] It has been reported that vitreous body injection of amikacin may lead to macular necrosis. [20,21] However, there are no effective antibiotics that can control infection through anterior chamber injection.…”
Section: Discussionmentioning
confidence: 99%
“…Of the few reports of N. farcinica eye infection, the therapeutic efficacy of mild keratitis is acceptable, while the efficacy for endophthalmitis is relatively poor. [3–5] In this study, we report a case of infectious scleritis involving the corneal limbus, which is suspected to be caused by N. farcinica in traumatic wound infection. The diagnosis was quickly and accurately confirmed by pathogenic microorganism culture and metagenomic sequencing.…”
Section: Introductionmentioning
confidence: 99%
“…The following [ 1 ] should be considered the version of record and used for citation purposes: “Neharika Sharma and Stephen O’Hagan, The role of oral co-trimoxazole in treating Nocardia farcinica keratitis: a case report. Journal of Ophthalmic Inflammation and Infection (2016) 6:21 DOI 10.1186/s12348-016-0087-y”.…”
Section: Correctionmentioning
confidence: 99%